Analysis of the pulmonary function of wind instruments musicians - Claudia Adriana Sant’Anna Ferreira; Maria Rita Montenegro Isern; Caroline Calanzo de Aquino Baroni; Vanderli Klouczek Carrocini (O Mundo da Saúde, 2010)
Wind instruments musicians need an effective respiratory muscular force and pulmonary function to produce sounds suitably, and they really need to have technical ability, breathing control and air pressure. The objective of this study was to evaluate the pulmonary function of wind instruments musicians and to compare it with musicians who play other instruments. The work was approved by the Ethics and Research Committee, Process 66/08. Volunteers signed the Term of Free Informed Consent, as well as a card of evaluation with weight, height, BMI, sex, tobacco addiction, musical practice and physical activity. We evaluated pulmonary function through manovacuometry and spirometry. A statistician analyzed data from a 5% significance value. 77 musicians from EMM of Sao Paulo, divided in two groups, study group (SG), with 51 musicians who play blowing instruments, and control group (CG), with 26 musicians who play other instruments. The result of the comparison of vital signs (cardiac and respiratory frequency and arterial pressure) has shown no statistical difference between the groups. Only arterial pressure was a little high in the sub-group tuba in relation to the other groups. Concerning pulmonary function, EG presented higher values than CG, in particular the sub-group tuba with CVF of 5.7 Ls, versus 4.5 Ls control (p =0,027), and the Pimax was statistically greater than the one of CG, with an average of 244cmH2O versus 142cmH2O (p = 0.017), respectively. We concluded that most wind instruments players (mainly the tuba) presented a better pulmonary function and a force in the respiratory musculature when compared with musicians of other modalities.